Insecticidal and antifeedant bioactivities of Melaleuca alternifolia essential oil on Ascia monuste orseis - MARTINS DA SILVA, Paulo Henrique; Prado, Evandro Pereira [UNESP]; Ferreira-Filho, Pedro José; Francisco, João Paulo; Del Quiqui, Erci Marcos; Silva, Camila; Guerreiro, Julio César (SAGE Publications, 2023)
The bioactive effects of Melaleuca alternifolia essential oil on the behavior and mortality of Ascia monuste orseis caterpillars were studied. The experiment was conduc-ted under controlled laboratory conditions using a completely randomized design with six treatments, represented by A. monuste orseis caterpillars fed on cabbage leaves treated with 0 (control), 5, 10, 20, 30, or 40 mg mL−1 essential oil. Treatments were applied to discs of collard leaves by immersion for 1 min. The leaves were offered to the insects ad libitum. Each treatment consisted of five replicates of four third-instar caterpillars. Mean daily intake of collard leaves, faeces production, mortality, and behavioral changes were assessed for 15 days after the beginning of the experiment. Data on leaf intake and faeces production were subjected to analysis of variance by the F-test; when significant differences were found, data were subjected to regression analysis. Corrected mortality rate was calculated and subjected to analysis of variance by the F-test followed by Tukey’s test at the 5 % significance level for comparison of means. The median lethal concentration (LC50) was also evaluated. Two very clear feeding behaviors were observed, one in caterpillars exposed to essential oil concentrations of 5, 10, and 20 mg mL−1, which showed little difference in leaf intake from the control, and the other in caterpillars exposed to the highest concentrations (30 and 40 mg mL−1), which showed a decrease of 76 % to 93 % in feed intake compared with the control. Lower leaf intake resulted in a decrease in faeces production, and the negative effects increased linearly with essential oil concentration. The mortality curve showed a linear and positive response to essential oil concentration, reaching 100% in insects exposed to the highest concentrations. The LC50 was 13.93 mg mL−1.
Bioactividades insecticidas y antialimentarias del aceite esencial de Melaleuca alternifolia en Ascia monuste orseis
Keywords: Bioinsecticide; cabbage; caterpillar; feeding deterrence; mortality; tea tree